Effect of recirculation ratio on the performance of modified septic tank in treating office building wastewater - Va Vandith; Setiyawan Ahmad Soleh; Soewondo Prayatni; Putri Dyah Wulandari (E3S Web of Conferences, 2020)
Higher concentration of nutrients has been characterized from office buildings compared to domestic wastewater. A Modified Septic Tank (MST), which consists of anoxic conditions followed by a Moving Bed Biofilm Reactor (MBBR) is proposed to treat office wastewater. This research investigated the effect of Recirculation Ratio (RR) on organic and nutrient removal in MST. The synthetic wastewater with COD: TN: TP (252:85:3), which is similar to actual office wastewater was used. The experimental data were obtained from three RR values (2, 3 and 4). The results showed COD, TN, NH4, and TP removal ranged from 88% to 90%, 64% to 78%, 68% to 86%, and 56% to 64%, respectively. The effluent concentrations of COD and NH4 ranged from 21 to 30 and 9 to 23 mg/L after applying RR and from 19 to 24 and 27 to 29 mg/L without RR, respectively. RR had the significant effect on organic and nutritional removal (p <0.05). It suggested increasing RR could improve nutrient removal in MST and the stability of NH4 in the effluent needs to be considered.